2015
DOI: 10.1083/jcb.201502078
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the yeast dynamin-like GTPase Sey1p provide insight into homotypic ER fusion

Abstract: The crystal structures of the N-terminal cytosolic domain of Sey1p shed light on the mechanism of Sey1p-mediated ER membrane fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 41 publications
5
63
0
Order By: Relevance
“…The hATL3 structure revealed a novel active site organization: whereas hATL1 (PDB 3Q5E), dmATL (PDB 3X1D), and Sey1 (PDB 5CA8) exhibit the same binding configuration for GDP•Mg 2+ (Byrnes and Sondermann, 2011; Wu et al, 2015; Yan et al, 2015), the canonical Mg 2+ was displaced by the guanidinium group of an intramolecular arginine residue at position 109 (R 109 ) in the hATL3 structure (Figures 6C and 6D), an active site residue that is distinct from the catalytic arginine finger (R 70 in hATL3, R 77 in hATL1). The conformation of R 109 is further stabilized through a salt-bridge formed with an aspartate residue at position 142, one of the main Mg 2+ -coordinating residues in ATLs (Figure 6C) (Bian et al, 2011; Byrnes and Sondermann, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hATL3 structure revealed a novel active site organization: whereas hATL1 (PDB 3Q5E), dmATL (PDB 3X1D), and Sey1 (PDB 5CA8) exhibit the same binding configuration for GDP•Mg 2+ (Byrnes and Sondermann, 2011; Wu et al, 2015; Yan et al, 2015), the canonical Mg 2+ was displaced by the guanidinium group of an intramolecular arginine residue at position 109 (R 109 ) in the hATL3 structure (Figures 6C and 6D), an active site residue that is distinct from the catalytic arginine finger (R 70 in hATL3, R 77 in hATL1). The conformation of R 109 is further stabilized through a salt-bridge formed with an aspartate residue at position 142, one of the main Mg 2+ -coordinating residues in ATLs (Figure 6C) (Bian et al, 2011; Byrnes and Sondermann, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…ATLs are resident to the tubular ER, where they catalyze membrane fusion to maintain ER morphology; proper control of this process is essential for axonal development, integrity, and signaling (Hu et al, 2009; Muriel et al, 2009; Orso et al, 2009; Rao et al, 2016; Renvoisé and Blackstone, 2010; Rismanchi et al, 2008; Yan et al, 2015; Li et al, 2017). Whereas hATL1 and hATL2 appear to be distributed throughout the tubular ER, hATL3 has a tendency to form puncta at tubule three-way junctions (Wang et al, 2016; Yan et al, 2015). hATL1 and hATL3 also localize to peripheral ER sheets and large sheet-like three-way junctions, and recently, super resolution microscopy techniques revealed that these structures are areas of dense tubular matrices (Nixon-Abell et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural studies of human ATL1 and Candida albicans Sey1p have provided significant insight into the mechanism by which these GTPases fuse membranes [30][31][32][33]. ATL and Sey1p/RHD3 contain an N-terminal GTPase and a helical bundle domain, followed by a TMH and C-terminal tail (CT).…”
Section: Fusion Of Er Membranesmentioning
confidence: 99%
“…At a subcellular level, the loss of RHD3 also reduces the formation of three-way junctions owing to the capacity of the protein to fuse membranes in a GTP-dependent fashion (Ueda et al, 2016). In this context, RHD3 functions analogously to similar membrane-associated dynamin-like GTPases, such as metazoan atlastin and yeast Sey1p Zhang et al, 2013;Yan et al, 2015). Nonetheless, it has been shown that the functional regulation of RHD3 may depend on plant-unique features.…”
Section: Er Dynamics Depend On the Cytoskeleton And Er-shaping Proteinsmentioning
confidence: 99%